KRAFTTERRA composite: Performance analysis of compressed earth blocks with and without cellulose pulp deriving from cement sacks recycling - Buson, M. (2009)
This study presents part of the results of an experimental campaign on the mechanical behaviour of Kraftterra composite. This research was developed as a framework of collaboration between the University of Brasilia, in Brazil, and the University of Aveiro, in Portugal. The objective of this study involves the development and the performance evaluation of compressed earthen blocks for the construction incorporating recycled cement sacks. Research’s main goal is the hypothesis verification that the cellulose pulp that stem from cement sacks can be used to improve the characteristics, and particularly the mechanical properties, of the blocks with soil as raw material. This paper presents the Kraftterra mixture and production processes, as well as the performance analysis of compressed earth blocks – CEBs – produced with Kraftterra regarding the compressive strength.